2021
DOI: 10.1080/17437199.2021.2016066
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of smartphone-based dietary assessment tools: a systematic review

Abstract: Smartphones have become popular in assessing eating behaviour in real-life and realtime. This systematic review provides a comprehensive overview of smartphone-based dietary assessment tools, focusing on how dietary data is assessed and its completeness ensured.Seven databases from behavioural, social and computer science were searched in March 2020.All observational, experimental or intervention studies and study protocols using a smartphone-based assessment tool for dietary intake were included if they repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 167 publications
(302 reference statements)
0
11
0
Order By: Relevance
“…Finally, the study lacks external validity because it was cross‐sectional and exclusively relied on questionnaires, also for assessing behavior, which have several shortcomings including recall bias (Naska et al, 2017; Thompson & Subar, 2017) that may distort the findings. A more in‐depth recording of eating behavior, for example, using smartphone‐based Ecological Momentary Assessment (König, Van Emmenis, et al, 2021; Shiffman et al, 2008), is needed to confirm the findings in real‐life settings.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study lacks external validity because it was cross‐sectional and exclusively relied on questionnaires, also for assessing behavior, which have several shortcomings including recall bias (Naska et al, 2017; Thompson & Subar, 2017) that may distort the findings. A more in‐depth recording of eating behavior, for example, using smartphone‐based Ecological Momentary Assessment (König, Van Emmenis, et al, 2021; Shiffman et al, 2008), is needed to confirm the findings in real‐life settings.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, self-report is the most feasible method in online studies. Nevertheless, future studies could consider new assessment methods such as photo-based recording (König, Van Emmenis, Nurmi, Kassavou, & Sutton, 2021 ) that may increase usability and reduce participant burden. Importantly, while absolute levels of target behaviors may be biased in our study, the goal attainment scores are informative, because both scores were measured with the same method within the same person, resulting in the same bias (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although only the free text recall was compulsory, previous work has demonstrated that the use of images in dietary assessments supports participant recall and increases reporting accuracy (Zhao et al, 2021 ). The use of food images and free text recall also supported the research team in the extraction of accurate nutritional information for specific products, and identification of portion sizes (where this information was not provided by participants) (see König et al, 2021 ). A combined time (free text recall) and event (image upload)‐based approach increases the accuracy and ecological validity of EMA assessments, as limitations associated with solely event‐based approaches (i.e.…”
Section: Methodsmentioning
confidence: 99%